1995
DOI: 10.1111/j.1365-2141.1995.tb05428.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of minimal residual disease in childhood acute lymphoblastic leukaemia using fluorescence in‐situ hybridization

Abstract: Using centromere-specific probes and a fluorescence in-situ hybridization (FISH) technique in cases of childhood hyperdiploid acute lymphoblastic leukaemia (ALL), cells with extra copies of chromosomes can be differentiated from normal cells by their extra signals in both metaphase and interphase nuclei. In this way the entire cell population, not only those cells in division, can be analysed, thereby providing a valuable technique not only for determining leukaemia cell karyotype at diagnosis but also for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In- terphase FISH is one of the sensitive techniques particularly suitable for studying cases with an HH karyotype [15,16]. In our study, remission was confirmed by FISH in all 12 patients studied.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In- terphase FISH is one of the sensitive techniques particularly suitable for studying cases with an HH karyotype [15,16]. In our study, remission was confirmed by FISH in all 12 patients studied.…”
Section: Discussionsupporting
confidence: 66%
“…This technique is especially useful in childhood ALL, which is characterized by nonrandom gains of whole chromosomes, leading to hyperdiploidy [11][12][13]. In addition, it has been proposed to detect minimal residual disease (MRD) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant density of surface markers on leukemic cells can be found for several markers like CD45 or CD34 (5). Beside aberrant combinations of surface markers, density measurements of antigens on leukemic cells can be helpful in the detection of minimal residual disease (3,6,7). The surface marker expression can be used to create an ''area of interest'' in the dot-plot derived by flow cytometric measurement where the malignant cells can be found.…”
mentioning
confidence: 99%